2010
DOI: 10.1111/j.1600-079x.2010.00752.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin treatment normalizes plasma pro‐inflammatory cytokines and nitrosative/oxidative stress in patients suffering from Duchenne muscular dystrophy

Abstract: Duchenne muscular dystrophy (DMD), a lethal disorder characterized by dystrophin absence, courses with chronic inflammation, sarcolemmal damage, and skeletal muscle degeneration. Among the multiple pathogenic mechanisms proposed for DMD, oxidative stress and inflammation are directly involved in the dystrophic process. Unfortunately, there is no current treatment for DMD, and the inflammatory process is an important target for therapies. Based on the antioxidant and anti-inflammatory properties of melatonin, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
116
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(121 citation statements)
references
References 62 publications
(101 reference statements)
3
116
0
2
Order By: Relevance
“…Melatonin (300 mg/day for up to 3 years) decreased oxidative stress in patients with amyotrophic lateral sclerosis [211] with very few undesirable side effects. In children with muscular dystrophy, 70 mg/day of melatonin reduced cytokines and lipid peroxidation [212]. Doses of 80 mg melatonin hourly for 4 h were given to healthy men with no undesirable effects other than drowsiness [213].…”
Section: Resultsmentioning
confidence: 99%
“…Melatonin (300 mg/day for up to 3 years) decreased oxidative stress in patients with amyotrophic lateral sclerosis [211] with very few undesirable side effects. In children with muscular dystrophy, 70 mg/day of melatonin reduced cytokines and lipid peroxidation [212]. Doses of 80 mg melatonin hourly for 4 h were given to healthy men with no undesirable effects other than drowsiness [213].…”
Section: Resultsmentioning
confidence: 99%
“…Melatonin has pleiotropic bioactivities including as a highly effective antioxidant and free radical scavenger (Beyer et al 1998, Gitto et al 2009, Chahbouni et al 2010, Paradies et al 2010. Melatonin has protective effect against heart and brain ischemia/reperfusion injuries depending on its antioxidant and free radical scavenging properties (Paradies et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin has a strong ability to suppress inflammation and modulate immune responses [14,38]. Melatonin has been shown to attenuate microglial activation after ischemia [39].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that melatonin has free radical scavenging and antioxidant functions [13]. It has the capability of scavenging free radicals and blocking transcription factors that induce proinflammatory cytokines [14]. These functions contribute to melatonin's antioxidant and anti-inflammatory properties in the diabetic setting [15].…”
Section: Introductionmentioning
confidence: 99%